Overall improvement in production drilling efficiency at Grootegeluk Coal Mine, to meet current and future drilling demand - Teffo, Ronald (My University, 2020)
Production drilling capacity at Grootegeluk mine needs to be sustained to ensure that the required floor stock levels of blasted material is maintained. Drill rig availability, utilisation and cycle time (hole to hole movement) of the drill rigs have an impact on the drilling output. Without blasted floor stock (blasted material which must be loaded by shovels into the haul trucks, mining operation will not be able to reach planned production target. Root cause analyses is utilised to address the question why production drill rigs at Grootegeluk mine are not performing as planned. It is also used to determine how Grootegeluk mine can avoid having the same problem in the future. Since 2014 the drilling fleet size at Grootegeluk increased to seven (three additional drill rigs procured) without adjusting the maintenance strategy. This resulted in the artisan/technician to equipment ratio decreasing from 1.5 to 0.86 and without the corresponding increase in supervision (Foreman and pit worker). There are multiple inefficiencies in the drilling section which lead to the poor performance of the section. To minimise or fully eliminate inefficiencies it is necessary to consider autonomous drilling. With autonomous drilling, operators are removed from the drill rigs and they are controlled remotely from a control room. Findings from the project indicted that, Grootegeluk maintenance and operational structures are not aligned to the number of drill rigs currently on the mine. Drill rigs were increased from four to seven, the maintenance team remained the same resulting in insufficient manpower to service and maintain the drill rigs. UoA dropped mainly due to the increase in a number of drill rigs on the mine without substantial increase in supervision. It is therefore, recommended that Grootegeluk take a phased approach in improving drill rig utilisation by correcting organisational structure first then replace the current drilling fleet with an autonomous fleet over a period of three years (2020 to 2022), this will improve utilisation from the current 49% to 72%
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering(Mining), 2020